Omega 3 fatty acid supplementation after myocardial infarction: A systematic review and meta-analysis - Popoff, Federico (2019)
Background: The purpose of this review is to examine the effect of Omega-3 Fatty acids on mortality, morbidity, and adverse events in patients with acute myocardial infarction (AMI). Methods: Data Sources: MEDLINE, EMBASE, and the Cochrane Library through May 2018. Study Selection: Randomized Controlled trials (RCT). Certainty of evidence was assessed with the GRADE system. Interventions: omega 3 fatty acids against placebo or no treatment. Primary and secondary outcomes: All-cause death, cardiovascular death, new AMI, stroke, need for therapeutic angioplasty or By-pass, new diagnosis of cancer and incidence of adverse events. Results: For the efficacy endpoints we included 10 RCT (24,414 patients). Omega 3 fatty acids probably make little or no difference to all-cause mortality (4 studies 9141 patients RR 1.06 - CI95% 0.90 to 1.27, moderate certainty), cardiovascular mortality (3 studies 4304 patients RR 0.93 - CI95% 0.63 to 1.37, moderate certainty), new AMI (RR 1.24 CI95% 0.71 to 2.14 - moderate certainty), any cardiovascular event (RR 0.95 95%CI 0.86 to 1.05; low certainty due to risk of bias and imprecision), and stroke (RR 1.2 95%CCI 0,66-2,19 - moderate certainty). Regarding adverse events, we are uncertain if Omega 3 fatty acids improve/reduce non severe adverse events (RR 1.39 95% CI 0.36 to 5.34; very low certainty). There is probably little or no difference in the outcome suspension due to adverse events (RR 1.19 CI 95% 0.97 to 1.47; moderate certainty). Conclusions: For adult patients with AMI, omega 3 fatty-acids probably yield no benefit to patient important outcomes.